(untitled) (Journal of Applied Oral Science, 2021)
Calcium aluminate cement (CAC) has been highlighted as a promising alternative for endodontic use aiming at periapical tissue repair. However, its effects on dental pulp cells have been poorly explored. Objective: This study assessed the impact of calcium chloride (CaCl2) and bismuth oxide (Bi2O3) or zinc oxide (ZnO) additives on odontoblast cell response to CAC. Methodology: MDPC-23 cells were exposed for up to 14 d: 1) CAC with 2.8% CaCl2 and 25% ZnO (CACz); 2) CAC with 2.8% CaCl2 and 25% Bi2O3 (CACb); 3) CAC with 10% CaCl2 and 25% Bi2O3 (CACb+); or 4) mineral trioxide aggregate (MTA), placed on inserts. Non-exposed cultures served as control. Cell morphology, cell viability, gene expression of alkaline phosphatase (ALP), bone sialoprotein (BSP), and dentin matrix protein 1 (DMP-1), ALP activity, and extracellular matrix mineralization were evaluated. Data were compared using ANOVA (α=5%). Results: Lower cell density was detected only for MTA and CACb+ compared with Control, with areas showing reduced cell spreading. Cell viability was similar among groups at days one and three (p>0.05). CACb+ and MTA showed the lowest cell viability values at day seven (p>0.05). CACb and CACb+ promoted higher ALP and BSP expression compared with CACz (p<0.05); despite that, all cements supported ALP activity. Matrix mineralization were enhanced in CACb+ and MTA. Conclusion: In conclusion, CAC with Bi2O3, but not with ZnO, supported the expression of odontoblastic phenotype, but only the composition with 10% CaCl2 promoted mineralized matrix formation, rendering it suitable for dentin-pulp complex repair.